Corrigendum to 'Artificial Knee Joint and Ski Load Simulator for the Evaluation of Knee Braces and Ski Bindings': [11th conference of the International Sports Engineering Association, ISEA 2016, Procedia Engineering, Volume 147 (2016) 220-227]. (2016) - Nusser, Michaela; Hermann, Aljoscha; Senner, Veit
Abstract : The authors regret that the following information has to be corrected in the publication. (1) Adding the author Peter U. Brucker (OrthoPlus, Munich, Germany) as third author. The correct list of authors is: Michaela Nusser, Aljoscha Hermann, Peter U. Brucker, Veit Senner (2) Our reference-crosslink given in the header of Table 1 as [26] is incorrect and should be the following one (not yet cited): [52] Arnold EM, Ward SR, Lieber RL, Delp SL. A Model of the Lower Limb for Analysis of Human Movement. Annals of Biomedical Engineering 2010;38(2):269–79. DOI 10.1007/s10439–009–9852–5. – ISSN 1573–9686 The authors would like to apologise for any inconvenience caused.